Utilization Of Electric Arc Furnace Steel Slag As Partial Replacement Of Raw Materials In Ceramic Tile - Teo, Pao Ter (2016)
In this project, electric arc furnace (EAF) steel slag (obtained from SSB) was utilized as partial replacement of raw materials in ceramic tile, as one of efforts to manage the slag in a more sustainable way. In Stage 1, EAF slag had consistent properties among six batches and therefore, suitable for use in ceramic tile production. In Stage 2, the EAF slag (40 – 60 wt.%), ball clay (30 – 60 wt.%), K-feldspar (10 – 20 wt.%) and silica (10 – 20 wt.%) were wet-mixed, followed by slurry’s drying, crushing of dried slurry, granulation, compaction and firing (1150 °C). Composition F (40 wt.% EAF slag – 30 wt.% ball clay – 10 wt.% K-feldspar – 20 wt.% silica) had the lowest water absorption (0.33%) and apparent porosity (0.78%), accompanied by highest bulk density (2.39 g/cm3) and MOR (55.38 MPa). Factors such as anorthite and wollastonite phases, porosity, glassy phase and micro-cracking affect the final properties. In Stage 3, modification of parameters such as slurry’s milling, variation of EAF slag (30, 40, 50 and 60 wt.%) and firing temperatures (1100, 1150 and 1180 °C) were executed to study functions of EAF slag in influencing ceramic tile formulation. General factorial design proved that amount of EAF slag and firing temperature significantly influenced final properties of tile. EAF slag also functions as fluxing agent to form glassy phase and contributed to formation of anorthite and wollastonite phases during sintering. Composition I (50 wt.% EAF slag – 50 wt.% ball clay, fired at 1180 °C) had the lowest water absorption (0.16%) and apparent porosity (0.48%), accompanied by highest bulk density (2.95 g/cm3) and MOR (92.42 MPa). Leaching test proved that both Compositions F (Stage 2) and I (Stage 3) were non-toxic and environmentally friendly. Upon benchmarking with commercial floor tiles and MS ISO13006:2014 Standard, both tiles were found suitable to be used as high durability green floor tile.